1981
DOI: 10.1071/bi9810491
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Regulators in the Ovarian Follicle

Abstract: Data generated within the last several years have shown that follicular fluid contains substances, presumably peptide in nature, which exert potentially important effects on granulosa cells and the oocyte. This review briefly summarizes the current evidence concerning the nature and importance of these putative regulators including the luteinization inhibitor, oocyte maturation inhibitor, inhibitors of the binding of luteinizing hormone and follicle stimulating hormone, stimulators of ornithine decarboxylase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

1982
1982
1996
1996

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 59 publications
0
10
0
3
Order By: Relevance
“…Many factors with a wide range of biological activities have been described in follicular fluid but few have been fully characterized (Hammond, 1981). Activity which will stimulate cell growth and division is present in follicular fluid, but little attention has been paid to inhibitors of cell division in comparison to inhibitors of gonadotrophin binding, steroidogenesis and oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors with a wide range of biological activities have been described in follicular fluid but few have been fully characterized (Hammond, 1981). Activity which will stimulate cell growth and division is present in follicular fluid, but little attention has been paid to inhibitors of cell division in comparison to inhibitors of gonadotrophin binding, steroidogenesis and oocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis proposes that dominant follicles reduce the availability of gonadotrophic support to other antral follicles by increasing the feedback inhibition of pituitary secretion of FSH with oestradiol and inhibin (Baird, 1983). A second, but not mutually exclusive, hypothesis is that there are ovarian regulators which act at the ovarian level to modify the number of large antral follicles allowed to develop (Hammond, 1981 Reproduction,37380 Nouzilly, France. We sought evidence for this concept by investigating ovine follicular fluid as a potential source of a non-steroidal inter-and intra-ovarian regulator. All follicles visible on the ovarian surface of ewes were ablated by electrocautery on Day 12 (Day 0 = day of oestrus) to reduce variability between sheep with respect to antral follicles > 0-5 mm and to enhance the growth potential of the remaining follicles.…”
Section: Introductionmentioning
confidence: 99%
“…This observation, coupled with variation in follicular response to standard exogenous doses of gonado¬ trophins has led to the belief that, while these hormones play a central role in folliculogenesis, their action at the ovary is modulated by intra-ovarian mechanisms Ledwitz-Rigby et al, 1981;Driancourt, 1991). It has been suggested that this intra-ovarian control may be exerted in part by inhibin (Findlay et al, 1981) or by variations in local steroid concentrations (Leung and Armstrong, 1980 Several other factors, such as luteinizing inhibitor (Channing et al, 1980), follicular-regulating protein (DiZerega et al, 1982), oocyte-maturation inhibitor (Lintern-Moore and Moore, 1979), luteinizing stimulator (Youglai, 1972) and fibroblast and epi¬ dermal growth factors (Hammond, 1981) have also been found in follicular fluid, and some of these factors may have a role in the intra-ovarian control of ovulation.…”
Section: Introductionmentioning
confidence: 97%
“…Saul Malozowski, FDA, HFD-510, Rockville, MD 20897, USA Several factors other than gonadotropins and steroids have been shown to regulate follicular maturation and hormonal secretion in the ovary (1-6). Insulin-like growth factor I (IGF-I) and the type I IGF receptor are present in the ovary, where they are believed to constitute part of a regulated intra-ovarian signalling system (1,(3)(4)(5)(6)(7)(8). Among other functions, IGF-I may synergize with the effects of FSH on steroidogenesis and promote coordination among tissue compartments (9).…”
mentioning
confidence: 98%